Human Infections with Borrelia miyamotoi , Japan - Sato, Kozue; Takano, Ai; Konnai, Satoru; Nakao, Minoru; Ito, Takuya; Koyama, Kojiro; Kaneko, Minoru; Ohnishi, Makoto; Kawabata, Hiroki (Emerging infectious diseases, 2014)
We confirmed infection of 2 patients with Borrelia miyamotoi in Japan by retrospective surveillance of Lyme disease patients and detection of B. miyamotoi DNA in serum samples. One patient also showed seroconversion for antibody against recombinant glycerophosphodiester phosphodiesterase of B. miyamotoi. Indigenous relapsing fever should be considered a health concern in Japan.